What Napoleon could not do - Nnuro, DK (Riverhead Books, 2023)
When siblings Jacob and Belinda Nti were growing up in Ghana, their goal was simple: to move to America. For them, the United States was both an opportunity and a struggle, a goal and an obstacle. Jacob, an awkward computer programmer who still lives with his father, wants a visa so he can move to Virginia to live with his wife--a request that the U.S. government has repeatedly denied. He envies his sister, Belinda, who achieved, as their father put it, "what Napoleon could not do": she went to college and law school in the United States and even managed to marry Wilder, a wealthy Black businessman from Texas. Wilder's view of America differs markedly from his wife's, as he's spent his life railing against the racism and marginalization that are part of life for every African American living here.